Uji Daya Serap Diapers Anti Ruam (Diapers Rash) Modifikasi Sabut Kelapa (Cocosnucifera) - Siti Mardiyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2019)
The World Health Organization (WHO) reported in 2012 that the prevalence of skin irritation (diaper rash) in infants was quite high at 25% due to the use of diapers. One of the causes of diaper rash is caused by low diaper absorption. Increased absorption of diaper can be done by increasing the absorbent ability of diapers to absorb baby urine. The natural absorbent that can be modified in baby diapers is coconut fiber. Cellulose content in coconut fiber has the ability to absorb liquid high enough. This potential can be applied to absorb urine and sweat so that it can reduce moisture in baby diapers. Diapers that have high absorption can prevent the occurrence of rashes in infants. This study aims to examine differences in absorbency of diapers. Without coconut fiber and coconut husk modification diapers.             This type of research is experimental. The population and sample of the study were baby diapers with a total sample of 32 which were divided into 2 groups namely baby diapers without coconut fiber and with modification of coconut fiber. Testing for diaper absorption is carried out in a laboratory manner by measuring the volume and time of absorption of fluids given to diapers to the saturation limit (leak). The data analysis technique uses the independent t-test. Based on the results of the independent t-test showed that there were significant differences in the amount of volume and time of absorption of fluids given to bunch diapers and with coconut fiber. Thus it can be concluded that there is a significant influence on the addition of coconut fiber to the absorption of fluid in baby diapers. Keywords: Diapers, Rash, Coconut Fiber.